Leadership in anesthesiology: not just a one man show - GA Senapathi, Tjokorda; Widnyana, IMG; Cindryani, Marilaeta (Bali Journal of Anesthesiology, 2017)
Anesthesiology had been one of highly skilled professional specialty with diversity of training but with a structured model of leadership culture. TheÂ culture which could be drawn back since medical training to become a medical doctor. School of medicine had already established a standard model of teaching and training. The tutoring method is implemented mostly based on classroom meetings in traditional basic lesson, bedside teaching for clerkship and internship and lately adopted method of case-based discussion